2016
DOI: 10.1186/s12991-016-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthymic affective temperament and hypertension are independent determinants of serum brain-derived neurotrophic factor level

Abstract: BackgroundBrain-derived neurotrophic factor (BDNF) has neuroprotective, proangiogenic and myogenic effects and, therefore, possibly acts as a psychosomatic mediator. Here, we measured serum BDNF (seBDNF) level in hypertensive patients (HT) and healthy controls (CONT) and its relation to affective temperaments, depression and anxiety scales, and arterial stiffness parameters.MethodsIn this cross-sectional study, affective temperaments, anxiety, and depression were studied with questionnaires (TEMPS-A, HAM-A, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In general population, a significant positive correlation was observed between plasma BDNF and diastolic blood pressure, and sexual differences were demonstrated in relation with different serum lipids (Golden et al 2010 ). As it was a cross-sectional study, it is unclear if these associations observed are casual or elevated plasma BDNF represents a compensatory response of the disrupted lipid metabolism and hypertension, but the elevation of serum BDNF in hypertension was confirmed by our study as well (Nemcsik et al 2016 ). Interestingly, in contrast, decreased endothelial BDNF expression was found in hypertension (Prigent-Tessier et al 2013 ), so the source of higher BDNF serum and plasma levels in hypertension is probably not the endothelial cells.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In general population, a significant positive correlation was observed between plasma BDNF and diastolic blood pressure, and sexual differences were demonstrated in relation with different serum lipids (Golden et al 2010 ). As it was a cross-sectional study, it is unclear if these associations observed are casual or elevated plasma BDNF represents a compensatory response of the disrupted lipid metabolism and hypertension, but the elevation of serum BDNF in hypertension was confirmed by our study as well (Nemcsik et al 2016 ). Interestingly, in contrast, decreased endothelial BDNF expression was found in hypertension (Prigent-Tessier et al 2013 ), so the source of higher BDNF serum and plasma levels in hypertension is probably not the endothelial cells.…”
Section: Introductionsupporting
confidence: 69%
“…We previously demonstrated that in chronic hypertensive patients with dominant irritable, anxious, cyclothymic and depressive affective temperaments, serum BDNF level was decreased compared with chronic hypertensive patients without dominant affective temperaments (Laszlo et al 2015 ). In chronic hypertensive patients, hyperthymic temperament score was found to be associated positively with serum BDNF level (Nemcsik et al 2016 ). As hyperthymic temperament score was found to be inversely associated with coronary atherosclerosis (Nemcsik et al 2017 ), it can be proposed that BDNF is a mediator of the protective effect of hyperthymic temperament in CV conditions.…”
Section: Introductionmentioning
confidence: 99%
“…BDNF, an important member of the neurotrophic factor family, is a protein synthesized in the brain and widely distributed in the central nervous system (CNS), as well as the peripheral nervous system (12). It can promote the survival, growth, differentiation, and development of neurons and plays a crucial role in the neural structure and functional plasticity (13, 14). A large number of human and animal studies have implicated the close links between BDNF and the occurrence and treatment of various diseases, including schizophrenia (15), Alzheimer's disease (16, 17), mood disorders (18), and Parkinson's disease (19).…”
Section: Bdnf and Mood Disordersmentioning
confidence: 99%
“…The higher frequency of hyperthymic temperament in women with infertility was an interesting finding of this study. In a study investigating the relationships between temperamental characteristics and brain-derived neurotrophic factor (BDNF) levels in patients with hypertension, high levels of BDNF were detected in patients with hyperthymic temperament, and a protective effect of hyperthymic temperament against hypertension through BDNF was suggested 30 . The central role of BDNF in neuronal growth is known, and it was shown in a meta-analysis that the reduced level of BDNF in major depressive disorder increases with antidepressant therapy 31 .…”
Section: Discussionmentioning
confidence: 99%